PENGEMBANGAN MEDIA PUZZLE BERBASIS ANDROID PADA MATERI PETUNJUK PENGGUNAAN ALAT - Dwi Puspowati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
The purpose of this study is to develop innovative, practical and effective learning media in Indonesian subjects with instructional materials for the use of tools. This research was motivated by the number of MI which did not have adequate learning media. This study uses the ADDIE development procedure with stages, Analysis, namely analyzing everything that includes needs and development, Design is making a framework, arrangement and appearance, Development includes the process of developing validation and revision media, Implementation is carried out in learning with media that has been developed and Evaluation, namely evaluating the media developed related to the level of effectiveness and attractiveness in learning. Data collection techniques used a questionnaire to assess the feasibility of the media and pretest and posttest questions to collect student value data. This research was conducted in class IV MI Qomarul Huda Banaran, Tembarak District, Temanggung Regency. The results of this study indicate that the Android-Based Puzzle learning media falls into the proper and effective category. This learning media was declared feasible based on the feasibility test according to media experts with a total percentage of 92% and valid material experts with a percentage of 81%. Whereas in its application, 32 students were able to increase the class average score from 68.33 to 86.7. So that the Android-based Picture Frame learning media is included in the valid, effective and feasible category to use.